An investigation into the molecular basis of familial forms of osteoarthropathy in South Africa - Ballo, Robea (Division of Human Genetics, 2017)
Generalised osteoarthritis (OA) is a common disorder of the joints which can lead to pain and disability. Identification of the determinant gene(s) is limited in part by the lack of Mendelian inheritance in most forms of the disorder, the combination of genetic and environmental influences and the late development of the condition. An approach to the investigation of the aetiology of OA would be to take advantage of the monogenic basis of inherited skeletal dysplasias in which OA is a major component. For this reason, the molecular genetic basis of the epiphyseal dysplasias, which encompass a spectrum of phenotypes ranging from mild to severe skeletal involvement, is addressed in this thesis. Familial skeletal disorders in South Africa in which OA is a major feature were identified and investigated using intragenic and closely linked microsatellite markers in order to determine linkage to candidate genes. Mutational analysis was undertaken to identify the genetic defect.